A locus at 7p14.3 predisposes to refractory celiac disease progression from celiac disease. Issue 8 (August 2018) - Hrdlickova, Barbara; Mulder, Chris J.; Malamut, Georgia; Meresse, Bertrand; Platteel, Mathieu; Kamatani, Yoichiro; Ricaño-Ponce, Isis; van Wanrooij, Roy L.J.; Zorro, Maria M.; Jan Bonder, Marc; Gutierrez-Achury, Javier; Cellier, Christophe; et al.
Abstract : Background: Approximately 5% of patients with celiac disease (CeD) do not respond to a gluten-free diet and progress to refractory celiac disease (RCD), a severe progression that is characterized by infiltration of intraepithelial T lymphocytes. Patients with RCD type II (RCDII) show clonal expansions of intraepithelial T lymphocytes that result in a poor prognosis and a high mortality rate through development of aggressive enteropathy-associated T-cell lymphoma. It is not known whether genetic variations play a role in severe progression of CeD to RCDII. Patients and methods: We performed the first genome-wide association study to identify the causal genes for RCDII and the molecular pathways perturbed in RCDII. The genome-wide association study was performed in 38 Dutch patients with RCDII, and the 15 independent top-associated single nucleotide polymorphism (SNP) variants ( P <5×10 −5 ) were replicated in 56 independent French and Dutch patients with RCDII. Results: After replication, SNP rs2041570 on chromosome 7 was significantly associated with progression to RCDII ( P =2.37×10 −8, odds ratio=2.36) but not with CeD susceptibility. SNP rs2041570 risk allele A was associated with lower levels of FAM188B expression in blood and small intestinal biopsies. Stratification of RCDII biopsies based on rs2041570 genotype showed differential expression of innate immune and antibacterial genes that are expressed in Paneth cells. Conclusion: We have identified a novel SNP associated with the severe progression of CeD to RCDII. Our data suggest that genetic susceptibility to CeD might be distinct from the progression to RCDII and suggest a role for Paneth cells in RCDII progression. Abstract : Supplemental Digital Content is available in the text.